2021
DOI: 10.24815/jts.v10i2.20727
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Kenaikan Tarif Ojek Online Terhadap Pendapatan Pengemudi Dan Kepuasan Penumpang, Tinjauan Sebelum Pandemi Covid 19

Abstract: Tariff and service are two important elements in online transportation. With the increase in rates, it will affect the income of drivers and passenger services. The purpose of this study is to determine the impact of the increase in online motorcycle taxi rates in 2019 when compared to 2018. Research in 2019 is a continuation of research in 2018. Data was obtained by conducting interviews with 200 passengers and 100 online motorcycle taxi drivers (Go-Jek) for each year. The impact of the tariff increase on dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Online motorcycle taxi rates have also increased because motorbikes need fuel oil to move the vehicle (Mallo & Nugroho, 2021;Farisi & Siregar, 2020). Previous research has shown that an increase in online motorcycle taxi fares has resulted in a decrease in online motorcycle taxi users (Risdiyanto et al, 2021;Siahaan et al, 2020).…”
Section: Uji Regresimentioning
confidence: 99%
See 1 more Smart Citation
“…Online motorcycle taxi rates have also increased because motorbikes need fuel oil to move the vehicle (Mallo & Nugroho, 2021;Farisi & Siregar, 2020). Previous research has shown that an increase in online motorcycle taxi fares has resulted in a decrease in online motorcycle taxi users (Risdiyanto et al, 2021;Siahaan et al, 2020).…”
Section: Uji Regresimentioning
confidence: 99%
“…The decision to increase online motorcycle taxi rates is contained in the Decree of the Minister of Transportation Number KP 564 of 2022 concerning Guidelines for Calculation of Service Fees for the Use of Motorcycles Used for Community Interests Done by Application (Risdiyanto et al, 2021). The adjustment to the motorbike usage fee, which will take effect on September 10, 2022, is carried out using an application based on a zoning system.…”
Section: Introductionmentioning
confidence: 99%
“…A. Latar Belakang Keputusan kenaikan tarif ojek online tertuang dalam Keputusan Menteri Perhubungan (KM) Nomor KP 564 Tahun 2022 Tentang Pedoman Perhitungan Biaya Jasa Penggunaan Sepeda Motor yang Digunakan untuk Kepentingan Masyarakat yang Dilakukan dengan Aplikasi (Risdiyanto et al, 2021). Penyesuaian biaya jasa penggunaan sepeda motor yang berlaku mulai 10 September 2022 ini dilakukan dengan aplikasi berdasarkan sistem zonasi.…”
Section: Pendahuluanunclassified
“…UU Nomor 14 Tahun 1992 menyebutkan untuk mencapai tujuan pembangunan nasional sebagai pengamalan Pancasila, transportasi memiliki posisi yang penting dalam pembangunan bangsa yang berwawasan lingkungan dan hal ini harus tercermin pada kebutuhan mobilitas seluruh sektor dan wilayah. Bahkan dalam sudut pandang ekonomi makro menyebutkan bahwa pengangkutan (transportasi) adalah salah satu prasarana yang sangat penting dan strategis dalam menunjang pelaksanaan pembangunan nasional dan memperlancar roda perekonomian (Maria Elisabeth Saubaki, 2019;Risdiyanto et al, 2021).…”
Section: Pendahuluanunclassified
“…Besarnya tarif layanan ditentukan oleh biaya biaya operasional yang mendukung layanan tersebut (Wulandari & Prihatini, 2018). Biaya-biaya itu seperti biaya transportasi, biaya promosi, biaya jasa pihak ke-3 serta biaya-biaya lainnya yang mendukung jasa atau layanan yang diberikan (Risdiyanto et al, 2021). Untuk tarif dasar layanan transportasi ditentukan oleh undang-undang yang mengatur mengenai biaya jasa.…”
Section: Kajian Pustakaunclassified